Pemberdayaan Siswa SMA Melalui Edukasi Kesehatan Gigi dan Mulut guna Meningkatkan Kualitas Hidup di Kota Semarang - Kusniati, Retno; Rakhmawati, Ayu Kristin; Ramadhani, Vania Putri (Jurnal Pengabdian UNDIKMA, 2026)
This community service activity aims to improve the quality of life related to dental and oral health in high school students through educational interventions and dental and oral health examinations. The implementation method of this service uses education and clinical examination practices of dental and oral health. The evaluation instruments for this activity are pre-test and post-test questionnaires to measure knowledge and a questionnaire to describe the quality of life related to dental and oral health. The results of this service indicate a very high caries prevalence (85.71%) and more than half of the students (54.29%) have an oral hygiene status (OHI) that requires attention. The educational intervention proved very effective, marked by a significant increase in the average score of students' knowledge from 72.3 to 93.7. From the quality of life aspect, although the majority of students did not report any problems, specific cases were found experiencing negative psychosocial impacts such as discomfort, embarrassment, and inferiority due to their dental condition. Education successfully increased student knowledge. However, in fact, based on examinations, there are still clinical problems with students' teeth and mouths. Therefore, a sustainable program is needed to encourage behavioral changes to significantly improve dental and oral health and students' quality of life.